From: sadoc on 28 May 2010 13:28 Hi, Thanks for the comments regarding the presentation. Now, the recursion is the following For i>=1, x[i + 1] = {[a + (i + 1)m]/a}.x[i] - (im/a).x[i - 1] - 1/a. When i=1, x[1] = x[0] - 1/a. Also, x[infinity] = 1/m and x[0] is the unknown quantity. Finally, x[-1] is not necessary and not well defined (as you suggested, we might take it to be infinite). Thanks! Best regards, Daniel On May 28, 1:14 pm, Ray Vickson <RGVick...(a)shaw.ca> wrote: > On May 28, 8:20 am, sadoc <danielsa...(a)gmail.com> wrote: > > > Hi, > > > thanks for the reply. Yes, the recursion I would like to solve is > > > x[i + 1] = (((a + (i + 1)m)/a).x[i]) - ((im/a).x[i - 1]) - (1/a) > > For your future reference: your equation is still unnecessarily hard > to read. You should strip off the brackets around separate terms and > just write > x[i + 1] = ((a + (i + 1)m)/a).x[i] - (im/a).x[i - 1] - 1/a. > > As long as you leave spaces around the separate terms, the '+' and '-' > signs will serve to delimit the different terms. Also, you might try > mixing bracket types when submitting equations written in ASCII, so it > would be even better to write > x[i + 1] = {[a + (i + 1)m]/a}.x[i] - (im/a).x[i - 1] - 1/a. > Do you see how much clearer that is? > > R.G. Vickson > > > > > I forgot to add the boundary conditions, though, > > > x[1] = x[0]-1/a > > This is a problem: if you put i=0 in the recursion (and assume x[-1] > is not infinite) you get x[1] = x[0]*(a+m)/a - 1/a. In order to have > x[1] = x[0] - 1/a you need (a+m)/a = 1, hence m = 0. So, either the > recursion fails for i = 0 or your boundary condition is wrong. > > R.G. Vickson > > > > > x[0] is unknown but > > > x[infinity] = 1/m > > > William, x[infinity]=1/m is in line with the solution you proposed.. > > However, I would like to cope with the boundary condition x[1]=x[0]-1/ > > a > > > Robert, using Maple, I was able to solve the recursion using > > > rsolve({x(n)=(1+(n)*m/a)*x(n-1) - ((n-1)* m/a)*(x(n-2)) - 1/a, > > x(1)=x0-1/a, x(0)=x0}, x(n)); > > > However, I get a very complicate solution, and I don't know how to > > cope with the condition x[infinity]=1/m > > > The motivation to the problem I'm trying to solve is the following: > > > consider a Markov chain with the following generator matrix > > > q(i,i+1) = a (i>=0) > > q(i,i-1) = im (i>=1) > > q(i,-1) = m (i>=1) > > > Question: given that we start in state s, s >=0, what is the mean time > > to reach state -1? > > > I think that this is related to birth-death processes with killing... > > > Thanks again! > > > Best regards, Daniel > > > On May 28, 5:20 am, William Elliot <ma...(a)rdrop.remove.com> wrote: > > > > On Fri, 28 May 2010, sadoc wrote: > > > > Please, how can I solve the following recursion? > > > > > x[ i + 1 ] = ( ( ( a + ( i + 1) m ) / a ) x[ i ] ) - ( ( i > > > > m / a ) x[ i - 1 ] ) - ( 1 / a ) > > > > Yicks. Is this what you wrote? > > > > x[i + 1] = (((a + (i + 1)m)/a).x[i]) - ((im/a).x[i - 1]) - (1/a) > > > > Besides needing to state a /= 0, it needs to be simplified. > > > > a.x[i + 1] = (a + (i + 1)m).x[i] - im.x[i - 1] - 1 > > > > A random thought occurs; > > > a(x[i + 1] - x[i]) = (i + 1)m.x[i] - im.x[i - 1] - 1 > > > > a(x[i + 1] - x[i]) = im(x[i] - x[i - 1]) + m.x[i] - 1 > > > > Let's solve the case m = 0. > > > > a(x[i + 1] - x[i]) = -1; x[i + 1] = x[i] - 1/a > > > > For all i in N, x[i] = x[0] - i/a is the solution. > > > > Regards the case m /= 0, > > > for all i in N, x[i] = x[0] = 1/m > > > is a solution. > > > > Let's examine the case for all i, x[i + 1] - x[i] = t. > > > > at = imt + m.x[i] - 1; m.x[i] = at - imt + 1 > > > > For all i, > > > x[i] = at/m + 1/m - it > > > isn't a solution if t /= 0, because > > > x[i + 1] - x[i] = -t, > > > contrary to the assumption > > > x[i + 1] - x[i] = t. > >
From: Ray Vickson on 29 May 2010 18:46 On May 28, 8:20 am, sadoc <danielsa...(a)gmail.com> wrote: > Hi, > > thanks for the reply. Yes, the recursion I would like to solve is > > x[i + 1] = (((a + (i + 1)m)/a).x[i]) - ((im/a).x[i - 1]) - (1/a) > > I forgot to add the boundary conditions, though, > > x[1] = x[0]-1/a > > x[0] is unknown but > > x[infinity] = 1/m > > William, x[infinity]=1/m is in line with the solution you proposed. > However, I would like to cope with the boundary condition x[1]=x[0]-1/ > a > > Robert, using Maple, I was able to solve the recursion using > > rsolve({x(n)=(1+(n)*m/a)*x(n-1) - ((n-1)* m/a)*(x(n-2)) - 1/a, > x(1)=x0-1/a, x(0)=x0}, x(n)); > > However, I get a very complicate solution, and I don't know how to > cope with the condition x[infinity]=1/m > > The motivation to the problem I'm trying to solve is the following: > > consider a Markov chain with the following generator matrix > > q(i,i+1) = a (i>=0) > q(i,i-1) = im (i>=1) > q(i,-1) = m (i>=1) <------ do you really mean you cannot get directly from state 0 to state -1? I will assume so below. If this is really your problem, I think you have the wrong recursion. If we let x[i] = expected time to reach the absorbing state -1 from state i >= 0 then I get: x[0] = (1/a) + x[1] x[1] = 1/(a + 2m) + [m/(a + 2m)]*x[0] + [a/(a + 2m)]*x[2] x[2] = 1/(a + 3m) + [2m/(a + 3m)]*x[1] + [a/(a + 3m)]*x[3], and in general: x[i] = 1/(a + (i+1)m) + [im/(a + (i+1)a)]*x[i-1] + [a/(a+(i+1)m)]*x[i +1] Maple 9.5 can solve this, but the result is very complicated. R.G. Vickson > Question: given that we start in state s, s >=0, what is the mean time > to reach state -1? > > I think that this is related to birth-death processes with killing... > > Thanks again! > > Best regards, Daniel > > On May 28, 5:20 am, William Elliot <ma...(a)rdrop.remove.com> wrote: > > > On Fri, 28 May 2010, sadoc wrote: > > > Please, how can I solve the following recursion? > > > > x[ i + 1 ] = ( ( ( a + ( i + 1) m ) / a ) x[ i ] ) - ( ( i > > > m / a ) x[ i - 1 ] ) - ( 1 / a ) > > > Yicks. Is this what you wrote? > > > x[i + 1] = (((a + (i + 1)m)/a).x[i]) - ((im/a).x[i - 1]) - (1/a) > > > Besides needing to state a /= 0, it needs to be simplified. > > > a.x[i + 1] = (a + (i + 1)m).x[i] - im.x[i - 1] - 1 > > > A random thought occurs; > > a(x[i + 1] - x[i]) = (i + 1)m.x[i] - im.x[i - 1] - 1 > > > a(x[i + 1] - x[i]) = im(x[i] - x[i - 1]) + m.x[i] - 1 > > > Let's solve the case m = 0. > > > a(x[i + 1] - x[i]) = -1; x[i + 1] = x[i] - 1/a > > > For all i in N, x[i] = x[0] - i/a is the solution. > > > Regards the case m /= 0, > > for all i in N, x[i] = x[0] = 1/m > > is a solution. > > > Let's examine the case for all i, x[i + 1] - x[i] = t. > > > at = imt + m.x[i] - 1; m.x[i] = at - imt + 1 > > > For all i, > > x[i] = at/m + 1/m - it > > isn't a solution if t /= 0, because > > x[i + 1] - x[i] = -t, > > contrary to the assumption > > x[i + 1] - x[i] = t. > >
From: sadoc on 1 Jun 2010 00:32 Dear R.G.Vickson, Thanks a lot for the answers. I found that the results in @Article{bdcata, title={On the first-visit-time problem for birth and death processes with catastrophes}, author={A. Crescenzo and V. Giorno and A. Nobile and L. Ricciardi}, year={2008}, journal={arXiv} } are actually very useful to solve this problem! They yield closed form expressions to the desired mean time to absorption. Follows below more comments. > > consider a Markov chain with the following generator matrix > > > q(i,i+1) = a (i>=0) > > q(i,i-1) = im (i>=1) > > q(i,-1) = m (i>=1) <------ do you really mean you cannot get directly from > > state 0 to state -1? I will assume > so below. Yes, we cannot go directly from 0 to -1. > > If this is really your problem, I think you have the wrong recursion. > If we let x[i] = expected time to reach the absorbing state -1 from > state i >= 0 then I get: > > x[0] = (1/a) + x[1] > x[1] = 1/(a + 2m) + [m/(a + 2m)]*x[0] + [a/(a + 2m)]*x[2] > x[2] = 1/(a + 3m) + [2m/(a + 3m)]*x[1] + [a/(a + 3m)]*x[3], > > and in general: > > x[i] = 1/(a + (i+1)m) + [im/(a + (i+1)a)]*x[i-1] + [a/(a+(i+1)m)]*x[i > +1] the equation above should be x[i] = 1/(a + (i+1)m) + [im/(a + (i+1)m)]*x[i-1] + [a/(a+(i+1)m)]*x[i +1] Yes, x[i] = 1/(a + (i+1)m) + [im/(a + (i+1)m)]*x[i-1] + [a/(a+(i+1)m)]*x[i +1] therefore, [a/(a+(i+1)m)]*x[i+1] = x[i] - 1/(a + (i+1)m) - [im/(a + (i +1)m)]*x[i-1] x[i+1] = x[i]/[a/(a+(i+1)m)] - [(a+(i+1)m)/a]/(a + (i+1)m) - - ([im/a]*x[i-1]) x[i+1] = x[i]/[a/(a+(i+1)m)] - 1/a - ([im/a]*x[i-1]) which is the recursion we originally started with > > Maple 9.5 can solve this, but the result is very complicated. yes... thanks a lot! Best regards, Daniel > > R.G. Vickson >
From: sadoc on 9 Jun 2010 18:44 The solution to the problem is at A note on birthdeath processes with catastrophes; by A Di Crescenzo et al. - 2008 -
First
|
Prev
|
Pages: 1 2 Prev: Godels seconded theorem ends in paradox-simple proof Next: Is this function convex? |